Vándorlások vizsgálata a szegedi agglomeráció egyik településén, 2010-ben - Zsótér, Brigitta; Nagy, Angéla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
A questionnaire survey wa s made on the migration to Deszk from which it can be concluded that the younge r and middle-.aged age group move to the settlement (65,19% migrated from Szeged). The reasons from migration are the low prices of plots and real estates and the peaceful environment. Most of the migrants work in Szeged and they used the settlement as a so-called ,.bedroom community" . A significant number of respondents (239 persons) drive to work. According to the analysis made by data of KSH, in the examined period (1999-2008) mortality exceeded birth rate, the number of marriages exceeded the numbe r of divorces. It can also be seen that more people migrate to Szeged and its catchment area than leave it.